Foreign experience of formation of innovative economy (Journal of Economic Research & Business Administration, 2016)
Dynamic development of the innovative sphere - one of main composed innovative economy. Such hi-tech economy assumes existence of effective innovative system and creation of institutes of support of innovative process. Each state with developed economy finds for itself own certain scenario of development and support of the national industry, being guided by development of innovative hi-tech productions. It is also important to take into account that the countries formed the policy during the different periods of time, having various competitive advantages. Many developing countries also placed emphasis on support of development of the innovative industries meaning the organization of hi-tech productions.The analysis of innovative development in Kazakhstan shows that in the country the big part is assigned to innovative activity. At the same time it should be noted that innovative activity in the republic isn't a source of increase of competitiveness of the country in the world market yet. One of problems of innovative development in Kazakhstan is incompleteness of scientific researches, their separation from production today.
Keywords: innovative economy; investment; industry; innovative activity; technology.